2018
DOI: 10.1155/2018/6578097
|View full text |Cite
|
Sign up to set email alerts
|

Traumatic Lumbosacral Dislocation: Current Concepts in Diagnosis and Management

Abstract: Traumatic lumbosacral dislocation is a rare, high-energy mechanism injury characterized by displacement of the fifth lumbar vertebra in relation to the sacrum. Due to the violent trauma typically associated with this lesion, there are often severe, coexisting injuries. High-quality radiographic studies, in addition to appropriate utilization of CT scan and MRI, are essential for proper evaluation and diagnosis. Although reports in the literature include nonoperative and operative management, most authors advoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 89 publications
0
24
0
Order By: Relevance
“…A combination of the more sagittal alignment of the lumbar facet joints, larger vertebral bodies, and surrounding paraspinal musculature means that a very large flexion distraction force is required to separate the lumbar facet joints. 5 In our case, a high-speed, off-center frontal collision generated the distractive and rotational forces necessary to explain the injury of a seat-belted passenger.…”
Section: Discussionmentioning
confidence: 74%
“…A combination of the more sagittal alignment of the lumbar facet joints, larger vertebral bodies, and surrounding paraspinal musculature means that a very large flexion distraction force is required to separate the lumbar facet joints. 5 In our case, a high-speed, off-center frontal collision generated the distractive and rotational forces necessary to explain the injury of a seat-belted passenger.…”
Section: Discussionmentioning
confidence: 74%
“…The injury has a high association with many other injuries including neurological deficits producing a multisystem impact. Both conservative and operative interventions have been described without consensus on the standard of care [1,[2][3][4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…The operative intervention has been associated with earlier mobilization and better mechanical stability acutely. However, there is a relatively high infection rate as could be expected due to the soft tissue damage [2][3][4]8,9,[10][11][12]. There is at least one case treated conservatively with late fixation reporting a favorable clinical outcome [1].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Most published reports and clinical series have shown that these injuries are commonly associated with motor vehicle accidents and are more prevalent in men than women, with an average age of around 27 years and typically bilateral dissociations with significant neurological deficits upon admission. The classification of complex lumbosacral injuries remains a controversial topic with various scoring systems taking into account the injury's morphology, posterior ligamentous complex integrity, and the patient's neurological status [1][2][3]. The severity of the injury results in chronic impairments, with early surgical intervention offering significant improvements in early mobilization, reduction in joint pain, mechanical stability, and possibly improved neurological outcomes [4][5].…”
Section: Introductionmentioning
confidence: 99%